2022
DOI: 10.5812/mejrh-129017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between COVID-19-related Factors and Self-management Behaviors in People with Type-2 Diabetes: A Cross-sectional Study

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a risk factor for long-term complications and mortality in people with diabetes. Diabetes self-management can prevent the adverse effects of COVID-19. Objectives: This study aimed to investigate the association between COVID-19-related personal, familial, and psychological factors and diabetes self-management. Methods: The research was conducted using the simple non-probability sampling method at the Institute of Endocrinology and Metabolism of Iran University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
2
Order By: Relevance
“…In contrast, other studies reported lower vaccination rates (4.8%) [31]. Overall, the rate in our study was unsatisfactory compared to studies from Saudi Arabia (84.8 %) [11], Turkey (73.6%) [32], and Iran (62.7%) [6]. This pointed to the lack of direct evidence that vaccinations benefit patients with diabetes, concerns about the vaccination's composition, and side effects that resulted in resistance to vaccine uptake among DM patients [31].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In contrast, other studies reported lower vaccination rates (4.8%) [31]. Overall, the rate in our study was unsatisfactory compared to studies from Saudi Arabia (84.8 %) [11], Turkey (73.6%) [32], and Iran (62.7%) [6]. This pointed to the lack of direct evidence that vaccinations benefit patients with diabetes, concerns about the vaccination's composition, and side effects that resulted in resistance to vaccine uptake among DM patients [31].…”
Section: Discussioncontrasting
confidence: 97%
“…Other laboratory parameters such as C-reactive protein (CRP), Ddimer, Procalcitonin (PCT), lactate dehydrogenase (LDH), and others are necessary for assessing disease severity [5]. Patients with comorbidities such as hypertension, diabetes mellitus (DM), heart disease, and respiratory disease are at a high risk of hospitalization and death [6]. Diabetic patients, especially those who are poorly controlled, are at an increased risk of severe clinical adverse effects, resulting from microbial infections, including respiratory viruses.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated 300 hospitalized COVID-19 patients with a variety of demographic, clinical, and laboratory profiles. In the current study, the vaccination coverage was 9.33%, which was low in comparison to studies from Iran, 14 Turkey, 15 Saudi Arabia, 16 and India. 17 On the contrary, only few studies reported a lower vaccination coverage for e.g.…”
Section: Discussioncontrasting
confidence: 87%
“…This increasing process of recovery rate and reduction of CFR may be due to the strengthening of the immune system and promotion of self-care by striving for a healthy lifestyle and consuming adequate nutrients (38,39), paying efforts to accelerate the development of treatment for COVID-19 by reusing antiviral drugs which are previously produced and approved by the FDA or currently assessed for other viral infections and combining these drugs with new technologies. These treatments aim to reduce the SARS-CoV-2 infection burden in patients, decreasing the severe symptoms and slowing down the COVID-19 improvement (40)(41)(42). For the most part, timely diagnosis and early treatment of infected cases are the first steps to winning this battle (13).…”
Section: Discussionmentioning
confidence: 99%